Alexa! : changing the face of Canadian politics - Kimber, Stephen (Goose Lane Editions, 2021)
A biography of Alexa McDonough, former leader of the Nova Scotia and federal NDP. Alexa McDonough's impact on Canadian politics cannot be measured solely by election victories or seat tallies. As the first female leader of a mainstream Canadian political party, she helped transform Nova Scotia and Canadian politics. In the process, she transcended party affiliation and gender to become simply "Alexa" to Canadians across the country. In this authorized biography, veteran author Stephen Kimber chronicles Alexa's life and political career and with it, weaves a narrative of the changing attitudes towards women in politics, from her early battles as the lone female MLA in a hostile Nova Scotian legislature to her leadership of the federal NDP to her role as senior stateswoman in Jack Layton's shadow cabinet. Along the way, Kimber delves into McDonough's personal life to uncover the origins of her political career. Her upbringing in a wealthy family committed to progressive politics, her tightknit circles of female friends, her personal metamorphosis from "wife-of" to "leader-of," and her emergence as a political leader whose importance goes beyond partisan politics. The result is an engrossing story of one of Canada's most beloved politicians, whose common touch and lifelong advocacy of progressive causes made her a significant player in Canadian public life.